Position Statement on Breastfeeding from the Italian Pediatric Societies. - Davanzo, Riccardo; Romagnoli, Costantino; Corsello, Giovanni (Ital J Pediatr, 2015)
The 2015 Position Statement on Breastfeeding of The Italian Pediatric Societies (SIP, SIN, SICupp, SIGENP) recognizes breastfeeding as an healthy behaviour with many short and long term benefits for both mother and infant.While protecting, promoting and supporting breastfeeding, neonatologists and pediatricians need specific knowledge, skills and a positive attitude toward breastfeeding. In Maternity Hospitals and in Neonatal Units, appropriate organizative interventions should be applied in order to facilitate the beginning of breastfeeding and the use of mother's/human milk.The Italian Pediatric Societies indicate the desiderable goal of around 6 months exclusive breastfeeding if the infant grows properly according to WHO Growth Charts. In principle, complementary feeding should not be anticipated before 6 months as a nutritional strategy pretending to prevent allergy and/or celiac disease. Eventually, long term breastfeeding should be supported meeting mother's desire.